2007
DOI: 10.4141/a06-073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary methionine to methionine plus cysteine ratios on nitrogen retention in gilts fed purified diets between 40 and 80 kg live body weight

Abstract: . 2007. Influence of dietary methionine to methionine plus cysteine ratios on nitrogen retention in gilts fed purified diets between 40 and 80 kg live body weight. Can. J. Anim. Sci. 87: [87][88][89][90][91][92]. The relationship between the ratio of available methionine (MET) to methionine plus cysteine (TSAA) intake and wholebody protein deposition (PD) was established using the nitrogen (N) balance technique in gilts between 40 and 80 kg live body weight (BW), according to a repeated 5 × 5 Latin square desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…It has been shown that the efficiency of SAA utilisation for PD is affected by dietary AA balance ( 34 ) . In a previous study ( 33 ) , it has been confirmed that SAA were among the first-limiting AA in the dietary AA profile that was used in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been shown that the efficiency of SAA utilisation for PD is affected by dietary AA balance ( 34 ) . In a previous study ( 33 ) , it has been confirmed that SAA were among the first-limiting AA in the dietary AA profile that was used in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…To our knowledge, this is the first attempt to evaluate SAA requirements and ileal digestibility of nutrients during ISS in growing pigs. In the present study, serial dilution of dietary protein sources was used to generate the dietary treatments and to avoid confounding of SAA intake levels with changes in dietary AA balance ( 33 ) . It has been shown that the efficiency of SAA utilisation for PD is affected by dietary AA balance ( 34 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Shoveller et al (2003) found that when Met is meeting 100% of the SAA requirement, Cys can replace 40% of the Met requirement. More recently, Gillis et al (2007) and Qiao et al (2008) suggested an optimal proportion of Met to SAA of 55.0% for growing pigs. In the basal diet of the current study, the SID Met : Cys ratio was 53 : 47 which is similar to the ratio that Yi et al (2006) used to determine the SID SAA requirement for nursery pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the optimal ratio of methionine to SAA, Gillis et al (2007) suggested an optimal ratio of 55.0% for 40-80 kg growing gilts. They investigated this ratio in relation to protein deposition using the nitrogen (N) balance technique.…”
Section: Figure 11 Fitted Linear-plateau Model (──) and Quadratic Modmentioning
confidence: 99%